Յատուկ անուններու տառադարձութեան խնդիրները արեւմտահայերէնի մէջ. պատմական զարգացումն ու զուգընթացութիւնը արեւելահայերէնի հետ - Ափոշեան, Աւետիս (ԳԱԱ ԼԻ հրատ․)
The article examines the fundamental differences between the two branches of the Modern Armenian language regarding the transcription of toponyms. While Armenian contains common place names inherited from Classical Armenian, the toponyms that are written differently in Western and Eastern Armenian languages are a result of their respective historical development processes. Western Armenian has predominantly borrowed new names from English (primarily) and French (to a lesser extent). In contrast, Eastern Armenians have mainly borrowed from the Russian language, as exemplified by cases such as “La Hague: Lahé (WA) / Haaga (EA)”. Additionally, we have recommended avoiding the use of the "ə" sound represented by the letter "ը" when transliterating English names. For instance, using “Լոս Անճելոս (Los Anjelos) rather than Լոս Անճելըս (Los Anjeləs)”. Our primary recommendations, based on theoretical foundations, are to implement standardised forms wherever possible and to reduce variations, first internally within each branch of the language, and then to work towards reconciling the differences between Western and Eastern Armenian branches. This study presents detailed categorisations of toponyms that we have classified, which, upon careful examination, provides guidance to professionals in the field and editors in determining the appropriate writing of place names. In the future, we are planning to prepare a publication in tabular format based on this research, presenting parallel forms in Classical Armenian, Western Armenian, Eastern Armenian with classical orthography, and Eastern Armenian with modern orthography.
Keywords: Արեւմտահայերէն; Տառադարձութիւն